Studi Dampak Pertumbuhan Ekonomi Terhadap Tingkat Pengangguran di Kota Jayapura - Ida Ayu Purba Riani; Putri Wahyuningsih (Universitas Cenderawasih, 2024)
This research aims to analyze the impact of economic growth on the unemployment rate in Jayapura City. The tool used to achieve this objective is regression analysis, which involves the variables of economic growth and unemployment rates over the period from 2013 to 2023. The results of the analysis indicate that the causal relationship between economic growth and unemployment is negative, meaning that an increase in economic growth tends to reduce the unemployment rate. However, this effect is only significant at the 10% significance level. The regression coefficient of -0.1102 suggests that a 1% increase in economic growth can reduce unemployment by 0.11%. Although 32.47% of the variation in unemployment can be explained by economic growth, other factors also play an important role. This study recommends the need for more comprehensive and inclusive policies, such as skills development, infrastructure development, and support for small and medium enterprises (SMEs), to create more effective job opportunities and reduce unemployment in Jayapura City. Key Words : Economic Growth, Unemployment, Regression Analysis